G430(P) Reducing the stress of starting paediatric specialty training. (May 2019) - Brothwell, SLC; Kelly, L; Bogue, D; Syrimi, E; Hine, C
Abstract : Aims: A significant amount of information needs to be disseminated to new ST1s at the start of Paediatric training, including information about the use of Supervised Learning Events, Kaizen, ARCP and general advice on training. Within our Deanery, information was previously delivered by individual Educational Supervisors and hospital induction sessions. Some trainees also benefited from informal advice from colleagues, but this was inconsistent and led to great variation in the quality and accuracy of the advice received by different trainees. The lack of consistent information and support had a huge impact on trainee satisfaction. To improve the trainee experience, develop the quality of training, and attempt to improve trainee retention, we created a bespoke 'Welcome to Paediatrics!' morning for new ST1s, with a programme designed to cover all vital aspects of training, including trainee wellbeing and sleep. Methods: Protected teaching time was negotiated from the Regional Teaching programme and all new ST1 trainees (n=22) were invited. Of these, 20 (91%) attended; the impact of the new programme was evaluated using a post-session questionnaire (response rate 100%). Results: Results showed that 85% of new trainees had worked in paediatrics previously; 40% of trainees were new to our Deanery. 100% of trainees strongly agreed/agreed that the Welcome! morning had helped them to feel more settled in the Deanery. Only 20% had received information about ARCP or Kaizen from another source. None of the trainees had received any information about sleep or wellbeing from their first hospital placement and only 20% had ever received information previously. Feedback demonstrated that 95% of trainees strongly agreed/agreed that it was useful to have dedicated time to discuss trainee wellbeing with more senior trainees. Conclusions: We have designed and implemented a new, trainee-led induction programme in order to deliver high quality guidance and support for new paediatric trainees. Information provided included the technical and logistical aspects of training, plus some traditionally neglected topics including sleep, trainee wellbeing, mentorship and career guidance. Feedback suggests that trainees found the session informative and useful; other Deaneries may benefit from setting up similar trainee-led Welcome! sessions.